Insurance Coverage and Utilization at a Sexually Transmitted Disease Clinic in a Medicaid Expansion State. Issue 5 (May 2017) - Montgomery, Madeline C.; Raifman, Julia; Nunn, Amy S.; Bertrand, Thomas; Uvin, A. Ziggy; Marak, Theodore; Comella, Jaime; Almonte, Alexi; Chan, Philip A.
Abstract : Background: In Rhode Island, the Patient Protection and Affordable Care Act has led to over 95% of the state's population being insured. We evaluated insurance coverage and barriers to insurance use among patients presenting for services at the Rhode Island sexually transmitted disease (STD) clinic. Methods: We analyzed factors associated with insurance coverage and utilization among patients presenting for STD services between July and December 2015. Results: A total of 692 patients had insurance information available; of those, 40% were uninsured. Patients without insurance were more likely than those with insurance to be nonwhite (50% among uninsured, compared with 40% among insured; P = 0.014) and Hispanic or Latino/a (25%, compared with 16%; P = 0.006), and less likely to be men who have sex with men (27%, compared with 39%; P = 0.001). Of those with health insurance, 26% obtained coverage as a result of the Affordable Care Act, and 56% of those were previously uninsured. Among uninsured individuals, barriers to obtaining health insurance included cost and unemployment. Among those with insurance, 43% reported willingness to use insurance for STD services. Barriers to insurance use included concerns about anonymity and out-of-pocket costs. Conclusions: Despite expanded insurance access, many individuals presenting to the Rhode Island STD Clinic were uninsured. Among those who were insured, significant barriers still existed to using insurance. STD clinics continue to play an important role in providing safety-net STD services in states with low uninsured rates. Both public and private insurers are needed to address financial barriers and optimize payment structures for services. Abstract : At a publicly funded sexually transmitted diseases clinic in a Medicaid expansion state, significant challenges to billing insurance for services still exist, including patient concerns about anonymity and cost-sharing via copays and deductibles.